VISION-RELATED QUALITY OF LIFE AND VISUAL FUNCTION AFTER RETINAL DETACHMENT SURGERY. Issue 5 (May 2016) - Smretschnig, Eva; Falkner-Radler, Christiane I.; Binder, Susanne; Spörl, Jessica; Ristl, Robin; Glittenberg, Carl; Krepler, Katharina
Abstract : Purpose: To investigate and compare the vision-related quality of life after rhegmatogenous retinal detachment (RRD) surgery with that of normal controls and to evaluate the relationship between the vision-related quality of life and visual function after surgery for RRD. Methods: In this prospective, consecutive, comparative case series, the 25-Item National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) was completed by 100 RRD patients at 6 months after surgery. Among the patients with RRD, 86 underwent pars plana vitrectomy and 14 received scleral buckling. Best-corrected visual acuity was obtained using ETDRS charts and converted to the logarithm of the minimum angle of resolution for statistical calculations. The VFQ-25 also was administered to 107 normal controls. Results: The VFQ-25 composite score and the subscales associated with general vision, mental health, social functioning, driving, and color vision were significantly lower in the RRD group than in the normal controls ( P < 0.05). The VFQ-25 composite score significantly correlated with logarithm of the minimum angle of resolution best-corrected visual acuity ( P < 0.0001) on both the operated and the fellow eye. Conclusion: The vision-related quality of life is significantly impaired in patients after surgery for RRD. Higher age and female gender negatively influences the results of the composite score. Abstract : Despite a successful surgery, significant differences concerning vision-related quality of life were observed in patients after rhegmatogenous retinal detachment surgery compared with a healthy control group.